2011
DOI: 10.1088/0004-637x/731/2/93
|View full text |Cite
|
Sign up to set email alerts
|

Star Clusters in the Tidal Tails of Interacting Galaxies: Cluster Populations Across a Variety of Tail Environments

Abstract: We have searched for compact stellar structures within 17 tidal tails in 13 different interacting galaxies using F606W -and F814W -band images from the Wide Field Planetary Camera 2 (WFPC2) on the Hubble Space Telescope (HST ). The sample of tidal tails includes a diverse population of optical properties, merging galaxy mass ratios, Hi content, and ages. Combining our tail sample with Knierman et al. (2003), we find evidence of star clusters formed in situ with M V < -8.5 and V -I < 2.0 in 10 of 23 tidal tails… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 99 publications
(153 reference statements)
5
60
0
Order By: Relevance
“…However, there could be a competition with the effects of azimuthal pileup, though this is likely to occur at an earlier time than the radial pileup. These considerations could explain the observed tendency for tails with relatively large dwarfs at their ends to have few clusters along their length, and vice versa (Knierman et al 2003;Maybhate et al 2007;Mullan et al 2011;Kaviraj et al 2012).…”
Section: Conjectures On Mechanisms Of Tidal Dwarf Formationmentioning
confidence: 99%
“…However, there could be a competition with the effects of azimuthal pileup, though this is likely to occur at an earlier time than the radial pileup. These considerations could explain the observed tendency for tails with relatively large dwarfs at their ends to have few clusters along their length, and vice versa (Knierman et al 2003;Maybhate et al 2007;Mullan et al 2011;Kaviraj et al 2012).…”
Section: Conjectures On Mechanisms Of Tidal Dwarf Formationmentioning
confidence: 99%
“…Is is sometimes observed that star-forming-regions in tidal tails are distributed in a beads-on-a-string morphology (Mullan et al 2011), that is, star formation takes place at spots about equidistantly distributed along the tidal tails. This supports an approximately homogeneous distribution of the formation sites of TDGs along the tails.…”
Section: The Mw Satellites As Tdgsmentioning
confidence: 99%
“…Hibbard et al 2001). Recently, Mullan et al (2011) used the Wide Field Planetary Camera 2 on the Hubble Space Telescope to search for compact stellar structures in the tidal tails of a sample of 13 interacting galaxies, where NGC 2782 was included. These authors found an absence of cluster candidates in the western tidal tail of NGC 2782; however, by using GALEX and Gemini data we have catalogued several star-forming region candidates, with ages <11 Myr, in the gaseous western tidal tail of this system.…”
Section: Tidal Tails: the Birthplace Of New Stellar Systemsmentioning
confidence: 99%